Simple Financial Management Counseling And Student Organization Management Training At Sekolah Tinggi Ilmu Kesehatan Al-Ma’arif Baturaja - Fitri, Yulita Eka (Jurnal Ekonomi, 2024)
STIKes Al-Ma'arif Baturaja is a private college located in Baturaja Timur District, Ogan Komering Ulu Regency. Many of the students have a poor understanding of financial planning. This community service aims to help students understand the basic principles of financial management while inspiring them to be young, creative, and innovative. Participants will learn about financial planning and how to stimulate creativity and innovation as young entrepreneurs. All first-year students of the DIII Nursing Study Program are the target audience for this community service involvement effort. These efforts include distributing educational materials and interactive discussions between facilitators and participants. Participants are expected to participate positively in all events from start to finish. Here are some of the anticipated consequences of this community participation initiative: Helping students in financial planning, To encourage students to pursue creative and innovative businesses, Making a list of needs and allowing participants to enter desired achievements and strategies to achieve them.